Perineal Pain Management with Cryotherapy after Vaginal Delivery: A Randomized Clinical Trial - Morais, Ítalo; Lemos, Andréa; Katz, Leila; Melo, Lorena Fernandes Rosendo de; Maciel, Mariano Maia; Amorim, Melania Maria Ramos de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Introduction Systematic reviews that evaluate the perineal cryotherapy to reduce pain in the vaginal postpartum are inconclusive.Purpose To evaluate clinical effectiveness of cryotherapy in the management of humanized postpartum perineal pain and vaginal edema.Methods A double-bind randomized controlled clinical trial (UTN number: U1111–1131–8433) was conducted in a hospital in Northeastern, Brazil. Women were included following humanized childbirth. All had vaginal deliveries of a single, full-term pregnancy with cephalic presentation. Exclusion criteria included previous perineal lesion, episiotomy during the current delivery, instrumental delivery, uterine curettage and postpartum hemorrhage. In the experimental group, an ice pack was applied six times on the perineum for 20 minutes, reducing the temperature between 10 and 15 ° C, then 60 minutes without exposure to cold. In the non-cryotherapy, a water bag unable to reduce the temperature to this extent was used, compliance with the same application protocol of the first group. Perineal temperature was monitored at zero, 10 and 20 minutes for application in both groups. Evaluations were made immediately before and after the applications and 24 hours after delivery spontaneous, to determine the association between variables.Results A total of 80 women were included in the study, 40 in each group. There was no significant difference in scores of perineal pain and edema between the groups with or without cryotherapy until 24 hours after childbirth. There was no difference between groups when accomplished repeated measures analysis over the 24 hours after delivery, considering the median perineal pain (p = 0.3) and edema (p = 0.9). Perineal cryotherapy did not influence the amount of analgesics used (p = 0.07) and no adverse effect was registered.Conclusion The use of cryotherapy following normal vaginal delivery within the concept of humanized minimally interventionist childbirth had no effect on perineal pain and edema, since it was already substantially lower, nor the need for pain medicaments.
Keywords: cryotherapy; pain management; perineum; postpartum period; natural childbirth